2018
DOI: 10.1007/s11325-018-1717-4
|View full text |Cite
|
Sign up to set email alerts
|

HLA-DQB1*06:02 allele frequency and clinic-polysomnographic features in Saudi Arabian patients with narcolepsy

Abstract: DQB1*06:02 allele frequencies among Saudi patients with narcolepsy were consistent with previously published data.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(3 citation statements)
references
References 35 publications
0
3
0
Order By: Relevance
“…Although there is no consensus on the mechanisms causing narcolepsy, the presence of auto-antibodies, HLA links, and familial predisposition point to autoimmune pathogenesis 32,33. Autoimmune diseases often demonstrate clinical improvement in the course of the disorders over time after an abrupt acute onset phase 34.…”
Section: Discussionmentioning
confidence: 99%
“…Although there is no consensus on the mechanisms causing narcolepsy, the presence of auto-antibodies, HLA links, and familial predisposition point to autoimmune pathogenesis 32,33. Autoimmune diseases often demonstrate clinical improvement in the course of the disorders over time after an abrupt acute onset phase 34.…”
Section: Discussionmentioning
confidence: 99%
“…Unlike HLA-A*11:01, HLA-DQB1*06:02 was expressed at significantly lower levels in SSNSWR and SDNS/FRNS than that in the control group. HLA-DQB1*06:02 allele and its high-frequency haplotypes have been previously reported to play different (risk/protection) roles in diseases of endocrine system, nervous system and immune system, thus indicating extensive and significant genetic effect [37][38][39][40][41][42]. In our study, low frequencies of HLA-DQB1*06:02 in SSNSWR and SDNS/FRNS suggested it to be a protective role in regulating the immune response and affecting the occurrence and development of the disease.…”
Section: Discussionmentioning
confidence: 99%
“…[34] In contrast, some other class II alleles had the greatest effect on narcolepsy risk, but 2 studies showed a small and independent effect of class I alleles. [35] 1.2.6. Orexin neurons may be killed by t cells.…”
Section: Evidence Of Autoimmune Mechanismsmentioning
confidence: 99%